Investigating the Existence of Egyptian Colloquial Arabic (ECA) in the Language Learning Context - Muhammad Lukman Arifianto; Iqbal Fathi Izzudin; Zulfa Azalia Mujahidah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2023)
Many scholars have discussed Egyptian Colloquial Arabic (ECA), especially concerning its structure and comparison with Standard Arabic, Modern or Classical. However, whether it is a phenomenon of language variation (diglossia) or it could be a language deviation from the Arabic grammatical rules has not been specifically explored. For this reason, this paper examines the ECA concerning its emergence and existence in Arabic language learning. Literature studies on several reference books and articles about ECA were carried out to present the views of experts regarding this discussion. Based on the results, it can be noted that there are two significant opinions regarding the existence of ECA in the language learning context. The scholars who posit that the ECA is a language deviation inherited the paradigm from the prescriptive study of language adopted by traditional linguistics schools. This perspective appeared as a consequence of the emergence and development of Arabic grammar, as well as the standardization of the language applied at that time. Meanwhile, the scholars who consider the ECA as a phenomenon of language variation tried to objectively portray and describe this language as they learned from the results of research on Egyptian sociolinguistics. This paradigm is in line with structural or modern linguistics which is more focused on the object of study. The results of this study can be used by Arabic language institutions & lecturers as consideration whether to include colloquial language elements in their Arabic teaching or not.